Evidence-Based Practice in physiotherapy: a systematic review of barriers, enablers and interventions - Scurlock-Evans, Laura; Upton, Penney; Upton, Dominic (Physiotherapy, 2014)
Despite clear benefits of the Evidence-Based Practice (EBP) approach to ensuring quality and consistency of care, its uptake within physiotherapy has been inconsistent. Synthesise the findings of research into EBP barriers, facilitators and interventions in physiotherapy and identify methods of enhancing adoption and implementation. Literature concerning physiotherapists’ practice between 2000 and 2012 was systematically searched using: Academic Search Complete, Cumulative Index of Nursing and Allied Health Literature Plus, American Psychological Association databases, Medline, Journal Storage, and Science Direct. Reference lists were searched to identify additional studies. Thirty-two studies, focusing either on physiotherapists’ EBP knowledge, attitudes or implementation, or EBP interventions in physiotherapy were included. One author undertook all data extraction and a second author reviewed to ensure consistency and rigour. Synthesis was organised around the themes of EBP barriers/enablers, attitudes, knowledge/skills, use and interventions. Many physiotherapists hold positive attitudes towards EBP. However, this does not necessarily translate into consistent, high-quality EBP. Many barriers to EBP implementation are apparent, including: lack of time and skills, and misperceptions of EBP. Only studies published in the English language, in peer-reviewed journals were included, thereby introducing possible publication bias. Furthermore, narrative synthesis may be subject to greater confirmation bias. There is no “one-size fits all” approach to enhancing EBP implementation; assessing organisational culture prior to designing interventions is crucial. Although some interventions appear promising, further research is required to explore the most effective methods of supporting physiotherapists’ adoption of EBP.